The Relationship between Demographical Characteristic and Central Obesity with Hypertension - Desy Amanda; Santi Martini (Universitas Airlangga, 2018)
Background: The prevalence of hypertension in Indonesia was 25,80% in 2013 found in people aged above 18 years old. One of the risk factors is obesity. Purpose: This study aimed to analyze the relationship between the demographical characteristic and central obesity with the risk of hypertension in the health center of Sidoarjo. Methods: This analytical observational study design was cross sectional. There were 50 respondents selected through accidental sampling. The independent variables of this study were respondents’ characteristic and central obesity status. However, the dependent variable was hypertension. Overall, respondents were divided into two groups based on sex (female and male) and age (> 59 years old and ≤ 59 years old). Data were analyzed with chi-square statistical analysis. Results: Respondents with central obesity had a higher risk to get hypertension, with majority male respondents aged above 59 years old. Conclusion: There was a correlation between age and hypertension (p = 0,01), sex and hypertension (p = 0,04), also between central obesity status and hypertension (p = 0,01).